A Virus Infecting Marine Photoheterotrophic Alphaproteobacteria (Citromicrobium spp.) Defines a New Lineage of ssDNA Viruses - Zheng, Qiang; Chen, Qi; Xu, Yongle; Suttle, Curtis A.; Jiao, Nianzhi (Frontiers in Microbiology, 2018)
In recent metagenomic studies, single-stranded DNA (ssDNA) viruses that infect bacteria have been shown to be diverse and prevalent in the ocean; however, there are few isolates of marine ssDNA phages. Here, we report on a cultivated ssDNA phage (vB_Cib_ssDNA_P1) that infects Citromicrobium bathyomarinum RCC1878 (family Sphingomonadaceae), and other members of the genus. This is the first ssDNA phage reported to infect marine alphaproteobacteria, and represents a newly recognized lineage of the Microviridae infecting members of Sphingomonadaceae, the Amoyvirinae. The ~26 nm diameter polyhedral capsid contains a 4,360 bp genome with 6 open reading frames (ORFs) and a 59.3% G+C content. ORF1 encodes the capsid protein and ORF3 encodes the replication initiator protein. The replication cycle is ~5 hours, followed by a burst releasing about 180 infectious particles. The closest relative of vB_Cib_ssDNA_P1 is a prophage within the genome of Novosphingobium tardaugens strain NBRC16725. Phylogenetic analysis indicates that the vB_Cib_ssDNA_P1 phage and two related prophages, as well as an environmental sequence, form a novel group within the Microviridae. Our results indicate that this is a previously unknown lineage of ssDNA viruses which also supplies a new model system for studying interactions between ssDNA phages and marine bacteria.